Management of large staghorn calculi – PCN Approach - Kempisty, Jakub; Pabiś, Szczepan; Ławiński, Janusz (Journal of Education, Health and Sport, 2020)
Urolithiasis is common condition affecting more than 10 % of well-developed country’s population. Formation of the stones may have few different causes. Stones can be classified by size, location, etiology, composition, and risk of recurrence. Evaluation of the stones should consist of imaging : X-Ray, CT, USG. When dealing with staghorn calculi PCN approach should be method of choice. This procedure is relatively safe and effective. In this paper we would like to present a case report of large and very hard complete staghorn calculi which was managed by the PCNL